PENGARUH IKLIM KOMUNIKASI ORGANISASI TERHADAP BUDAYA ORGANISASI Di PT ASKRINDO CABANG SURAKARTA - Sri Wahyu Ening Handayani (Jurnal Ilmu Komunikasi PROGRESSIO, 2021)
This research was made to see and measure the existence of dynamic organizational changes characterized by the transfer of employess from one company to another or other organizations to get comfortable at wor, welfare, and by the motivation of the vision and mission that exist in employees and the presence of a crisis. There is a breakdown of the patterns, beliefs, and structures that underline the old culture. This research is quantitative, data collection techniques using a closed questionnaire, to employees at PT Askrindo (Persero) Surakarta city branch. Data analysis using simple linier analysis, the data source is processed using the SPSS statistical application. The result showed that there was a significant influence of organizational communication climate on organizational culture, so the hypothesis (Ha) can be proven. The amount of influence of the indepent variable (organizational communication climate) in influencing the dependent variable (organizational culture) is determined by the R Square value of 20.1%. This means that the influence is given by the predictor variable (organizational communication climate) on the criterion variable (organizational culture) is 20.1%, while the remaining 79.9% is influence by other variables not examined.